Strategi Penghidupan Berkelanjutan Masyarakat Sekitar Kawasan Hutan Di Pulau-Pulau Kecil (Studi Kasus Di Pulau Maitara Provinsi Maluku Utara) - Kurniawan, Andy; Nurdin, Aqshan Shadikin; Ryadin, Aisjah Rachmawaty; Rosita, Rosita (Cannarium, 2022)
The livelihoods of people in small islands are never disconnected from socio-economic problems and the degraded environment. In the long term, the living system will influence the surrounding environmental condition if the environment utilization is not sustain managed. This research aimed to assess the people's livelihood assets to encourage the living quality of local people. Qualitative and quantitative methods were implemented to analyze the data from questionnaires in deeply direct interviews. The variables to evaluate in the livelihood assets condition consisted of human capital, natural capital, social capital, physical capital, and financial capital, which covered the sampling region in South and North Maitara island. The basic capital of people's livelihood is presented as Pentagon Assets, and its strategies are grouped into intensification, extensification, and migration. The result showed that the component of livelihood capital assets depending on natural capital was 8.99, financial capital was 9.88, physic capital was 12.38, human capital was 15.06, and social capital was 16.64. The intensification and extensification consisted of the percentage of yard utilization was 11%, agriculture land utilization was 37%, empty land utilization was 24%, and arable land utilization was 12%. Moreover, migration as part of livelihood strategies in this region composed of permanent migration was 15%, and circular migration or commuter was 45%. In conclusion, agricultural land utilization is still dominant for local people, exerting circular migration to sustain their subsistence.Keywords: livelihood assets, sustain, environment utilization, small island